DNA Methylation Profiles and Their Diagnostic Utility in BC. (6th May 2019) - Shan, Ming; Zhang, Lei; Liu, Yang; Gao, Chunyang; Kang, Wenli; Yang, Weiwei; He, Yan; Zhang, Guoqiang
Abstract : Biomarkers, including DNA methylation, have shown a great potential for use in personalized medicine for BC and especially for the diagnosis of BC in developing countries. According to the bisulfite sequencing PCR in twelve specimens (BC and matched normal tissues), nine genetic probes were designed to detect the frequency of methylation of the promoters in a total of 302 paired cases of BC and matched normal breast tissues. Finally, a total of 900 serum samples were used to validate the use of these methylation biomarkers for clinical diagnosis of BC. A high frequency of promoter methylation of SFN, HOXA11, P16, RARβ, PCDHGB7, hMLH1, WNT5a, HOXD13, and RASSF1a was observed in BC tissues. The methylation frequencies of HOXD13 and hMLH1 increased with the progression of BC. The methylation frequencies of HOXD13 and WNT5a were significantly higher in BC. We found that methylation modification-positive samples were most consistently associated with luminal BC. Finally, we confirmed that RASSF1a, P16, and PCDHGB7 displayed a significant sensitivity and specificity as diagnostic biomarkers for BC (P < 0.001 ), and a panel that combined these three genes displayed increased significance (AUC, 0.781;P < 0.001 ). These data suggest that epigenetic markers in serum can potentially be used to diagnose BC. The identification of additional BC-specific methylated genes would improve the sensitivity and specificity of this approach. This study could also indicate that different molecular subtypes of BC are caused by distinct genetic and epigenetic mechanisms.